173k views
2 votes
Solve the equation 2x+4(x-6)=3(2x-8)
Thank you

2 Answers

4 votes

Answer:

No solutions I think

Explanation:

2x + 4(x -6) = 3(2x -8)

2x + 4x -24 = 6x - 24

6x - 24 = 6x - 24

-6x +24 -6x +24

0 = 0

Hopefully this helped :)

User Thaller
by
5.8k points
7 votes

Answer:

IMS aka infintely many solutions :)

Explanation:

2x+4(x-6)=3(2x-8)

distribute

2x+4x-24=6x-24

combine like terms

6x-24=6x-24

carry across equal sign

6x=6x

carry across equal sign

0=0 aka IMS

User Maurice Gilden
by
4.9k points